Preliminary study about the possible glycemic clinical advantage in using a fixed combination of Berberis aristata and Silybum marianum standardized extracts versus only Berberis aristata in patients with type 2 diabetes - Di Pierro F; Putignano P; Villanova N; Montesi L; Moscatiello S; Marchesini G (Dove Medical Press, 2013)
Francesco Di Pierro,1 Pietro Putignano,2 Nicola Villanova,3 Luca Montesi,3 Simona Moscatiello,3 Giulio Marchesini3 1Scientific Department, Velleja Research, Milano, Italy; 2Outpatient Diabetic Clinic, University Hospital San Gerardo, Monza, Italy; 3Diseases of Metabolism, S Orsola Malpighi Hospital, Bologna, Italy Background: Berberine is an isoquinoline alkaloid widely used to improve the glucidic and lipidic profiles of patients with hypercholesterolemia, metabolic syndrome, and type 2 diabetes. The limitation of berberine seems to be its poor oral bioavailability, which is affected by the presence, in enterocytes, of P-glycoprotein – an active adenosine triphosphate (ATP)-consuming efflux protein that extrudes berberine into the intestinal lumen, thus limiting its absorption. According to some authors, silymarin, derived from Silybum marianum, could be considered a P-glycoprotein antagonist. Aim: The study aimed to evaluate the role played by a possible P-glycoprotein antagonist (silymarin), when added to a product containing Berberis aristata extract, in terms of benefits to patients with type 2 diabetes. Methods: The study enrolled 69 patients with type 2 diabetes in suboptimal glycemic control who were treated with diet, hypoglycemic drugs, and in cases of concomitant alterations of the lipid profile, hypolipidemic agents. The patients received an add-on therapy consisting of either a standardized extract of Berberis aristata (titrated in 85% berberine) corresponding to 1,000 mg/day of berberine, or Berberol®, a fixed combination containing the same standardized extract of Berberis aristata plus a standardized extract of Silybum marianum (titrated as .60% in silymarin), for a total intake of 1,000 mg/day of berberine and 210 mg/day of silymarin. Results: Both treatments similarly improved fasting glucose, total cholesterol, low-density lipoprotein (LDL) cholesterol, triglyceride, and liver enzyme levels, whereas glycosylated hemoglobin (HbA1c) values were reduced to a greater extent by the fixed combination. Conclusion: The association of berberine and silymarin demonstrated to be more effective than berberine alone in reducing HbA1c, when administered at the same dose and in the form of standardized extracts in type 2 diabetic patients. Keywords: Berberol®, P-glycoprotein, cholesterol, triglycerides, glycosylated hemoglobin